Studi Identifikasi Faktor-faktor yang Mempengaruhi Motivasi Kerja Karyawan Koperasi Unit Desa Beringin Jaya I - Afrizal Rangkuti; Yunita Yunita (Jouska: Jurnal Ilmiah Psikologi, 2023)
This study aims to describe the Study of the Factors Influencing Employee Motivation in Beringin Jaya I Village Cooperative Unit. The research method used is a method with a descriptive quantitative approach. The samples in this study were KUD Makmur Jaya employees in Beringin Jaya Village with a total sample of 51 people. Sampling using total sampling technique. The work motivation scale is compiled based on factors that influence work motivation according to Maslow (in Kristanti, 2019) factors that influence work motivation, namely: Physiological Needs, Need for a sense of security (Safety and Security Needs), Social needs or affiliation ( affiliation or acceptance Needs), Needs that reflect self-esteem (Esteem or Status Needs), Self-actualization needs (Self-Actualization), The highest factor that influences work motivation is the factor of the need for a sense of security giving the largest contribution, namely 81.70%., The smallest factor that is influencing work motivation is the need for self-actualization which is equal to 42.50%.